1991
DOI: 10.1136/jnnp.54.8.710
|View full text |Cite
|
Sign up to set email alerts
|

Central sleep apnoea in congenital muscular dystrophy.

Abstract: A sural nerve biopsy did not show significant abnormalities. CT and MRI scans of the brain were both normal.The patient was sent home with a PLV 100 ventilator and a nasal mask. There was dramatic improvement in her daytime performance and she has returned to work. A repeat sleep study on the ventilator a month later showed no sleep-disordered breathing and normal sleep architecture. Awake arterial blood gases were normal six months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 23 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Pulmonary function studies revealed that 19 (68%) of the 28 patients who underwent spirometry studies had restrictive syndrome ( PSG data for TST and percentage of sleep stages were compared with data taken from a review of current literature 31 , revealing that 64,5% (20) of our patients experienced a decrease in TST; 61,3% (19) had an increase in percent of stage 1 sleep and that 77,4% (24) experienced a reduction in percent of REM sleep.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Pulmonary function studies revealed that 19 (68%) of the 28 patients who underwent spirometry studies had restrictive syndrome ( PSG data for TST and percentage of sleep stages were compared with data taken from a review of current literature 31 , revealing that 64,5% (20) of our patients experienced a decrease in TST; 61,3% (19) had an increase in percent of stage 1 sleep and that 77,4% (24) experienced a reduction in percent of REM sleep.…”
Section: Resultsmentioning
confidence: 95%
“…The other 26 (81%) snored between 6 and up to 97% of their TST. Sleep disruption represented by an elevated number of movement arousals (MA) was observed in 5 patients ( Patients 3,10,19,23,26). All of these presented frequent snoring.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuromuscular disorders, particularly Duchenne's and other forms of muscular dystrophy [6,7,[95][96][97][98][99][100][101][102], are also typically associated with hypoventilation, which becomes more severe as the disease progresses [101,102], particularly during sleep. Muscular dystrophy produces respiratory insufficiency because of progressive degeneration of the muscles of respiration, and respiratory failure is the major cause of death in this condition, although cardiomyopathy due to degeneration of cardiac muscle is also a common finding [103].…”
Section: Neurological and Neuromuscular Disordersmentioning
confidence: 99%